2D Quantitative Analysis of Metal Foaming Kinetics by Hot‐Stage Microscopy1. Issue 1 (19th August 2013) - Duarte, Isabel; Ferreira, José M.F.
<x xml:space="preserve">Abstract</x> Hot‐stage microscopy commonly used in materials science, coupled with image analysis software (ImageJ) is proposed for the first time as an alternative and simple approach for visualizing the metal foam evolution and the thermal events occurring onto the external surface skin, as well as to obtain the expansion curve of foamable precursor material prepared by powder metallurgical method. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>